Reverse squeeze-out i sell-out w świetle przepisów Kodeksu spółek handlowych - Delczyk, Dominik (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The subject of the article are legal institutions designed to counterbalance squeeze-out’s regulations. The article presents the legal structure of reverse squeeze-out and sell-out, ratio legis and tax issues of the institutions.
Keywords: reverse squeeze-out; sell-out; shareholders; stock company; Code of Commercial Companies